Organizational Escalation and Retreat in University Athletics - Adrien Bouchet; Michael Hutchinson (University of Kansas Libraries, 2011)
This case study will explore the theory of escalation of commitment within the context of intercollegiate athletics. This management-based theory has been used within business and foreign policy literature, but has yet to be explored through a sport management context. Recently, Birmingham-Southern College chose to reclassify its athletics programs from the Division I classification to the Division III classification. Utilizing qualitative methodology, interviews (N = 11) were conducted with a variety of university constituents. Findings revealed the following four themes: a) unsubstantiated outcomes regarding the benefits of Division I athletics, b) strained finances, c) presidential leadership, and d) perceived roles of a small, liberal arts institution. Discussion and application of the resulting thematic emergences with the escalation of commitment determinants will be discussed.